Graphene nanostructures toward clean energy technology applications - Zhang, X.; Wang, B.; Sunarso, J.; Liu, Shaomin; Zhi, L. (John Wiley & Sons, Inc., 2012)
Graphene, a one-atom-layer-thick carbon-structured material, has attracted global research attention due to its unique two-dimensional structure, high electrical conductivity, superior electron-transfer properties and charge-carrier charge-carrier mobility, large specific surface area, high transparency, and good mechanical properties. After its successful isolation into the free standing form in 2004, various graphene nanostructures have been developed and incorporated as key components in supercapacitors, lithium-ion batteries, solar cells, and fuel cells; the energy supporting devices which hold the key role to sustain our energy demand well into the future. Herein, we summarized the recent progress and performance of these graphene–nanostructure-based devices.